224. Effect of Easing Overnight Restrictions on Antimicrobial Starts. (31st December 2020) - Yarrington, Michael E; Wrenn, Rebekah; Spivey, Justin; Shoff, Christopher; Spires, Steven S; Turner, Nicholas A; Smith, Michael J; Diez, Anthony; Anderson, Deverick J; Moehring, Rebekah W
Abstract: Background: Some institutions allow administration of restricted antibiotics overnight until evaluation the following day (i.e. first dose free) to adapt to limitations in personnel resources. Whether this method results in higher number of overnight requests compared to strict 24/7 preauthorization has not been fully described. Methods: In October 2019, Duke University Hospital (DUH) changed from strict preauthorization to allow initiation of two restricted agents (meropenem and micafungin) between the hours of 11pm to 7am. We performed an interrupted time series (ITS) analysis to evaluate the phase shift and change in trend in the number of new meropenem and micafungin orders per week before (Jan 2019-Oct 2019) and after (Oct 2019- Mar 2020) the process change. First antimicrobial orders for meropenem and micafungin were counted for unique patient encounters. We fit a Gaussian distribution function to the number of orders per hour of day to estimate the percent of orders initiated overnight (11p-7a) and during day/evening hours (7a-11p) before and after the process change. Results: Hospital data included 1728 new meropenem and micafungin orders over a 61-week period (~28 per week). The total number of meropenem and micafungin orders was constant between Jan 2019 and October 2019 (+0.07 orders/week, 95% CI -0.13 to 0.27, Figure 1) and the phase shift during the first week of October was non-significant (-4.38 orders, 95% CI -12.34 to 3.58). The number of orders increased after October 2019 (+0.70 orders/week, 95% CI 0.13 to 1.25), however a sensitivity analysis removing the largest outlier eliminates significance. The percent of total orders between 11am to 7pm increased from 13.3% to 17.2% after the intervention (Figure 2). Overall antibiotic use remained similar through the study period. Figure 1. Estimated Approvals per Week Figure 2. Approvals by Hour of Day Conclusion: There was no significant immediate change in overnight prescribing of meropenem and micafungin, however a trend towards increased number of orders appeared after removing overnight restriction requirements. Instead of "stealth dosing", where providers wait to enter restricted antibiotic orders until evening hours, we observed a small increase in starts in early morning hours (1am-6am). Preauthorization approaches must adapt to personnel resources and quality of life for antimicrobial stewards. Disclosures: Michael J. Smith, MD, MSC.E, Kentucky Medicaid (Grant/Research Support)Merck (Grant/Research Support) Rebekah W. Moehring, MD, MPH, Agency for Healthcare Quality and Research (Grant/Research Support)Centers for Disease Control and Prevention (Grant/Research Support)